"Green" method for monitoring the mineral composition of spring waters based on the results of double measurement of specific electrical conductivity. Issue 2 (November 2020) - Vasyukov, A E; Surinova, K K; Zinoviev, N R; Nikulina, S N; Chudakova, T A
Abstract: The "green" method of conductometric determination of the double dilution coefficients has been tested according to the results of monthly measurements during the year of the specific electrical conductivity of undiluted and twice diluted underground water from 4 springs. The first coefficient characterizes the ratio of mono- and divalent cations and anions in the water under study, the second one characterizes the content of dissolved salts in mg-eq/dm 3, which makes it possible to establish the hydrochemical type of the water under study. The technique can be classified as environmentally friendly since natural diluted distilled water serves as waste.